TOWARDS THE AUTOMATION OF MODEL‐BASED DESIGN VERIFICATION. Issue 1 (6th April 2017) - Schamai, Wladimir; Albarello, Nicolas; Helle, Philipp; Buffoni, Lena; Fritzson, Peter
ABSTRACT: Modeling and simulation of complex systems is at the heart of any modern engineering activity. Engineers strive to predict the behavior of the system under development in order to get answers to particular questions long before physical prototypes or the actual system are built and today tested in real life. One of the critical questions is whether a particular system design fulfills or violates requirements imposed on the system under development. In this paper, we discuss an approach to model‐based design verification by simulating system dynamic behavior including formalized requirements. We illustrate the approach on a case study – the verification of a new design for flight control surfaces activation against requirements. The contributions of this paper are the evaluation of a new requirements formalization approach using the recently developed Modelica requirements library, and the discussion of solutions for automating the simulation model composition.